Remember me [videorecording (DVD)] - Coulter, Allen; Pattinson, Robert, 1986-; De Ravin, Emilie, 1981-; Brosnan, Pierce; Cooper, Chris, 1951-; Olin, Lena (Summit Entertainment, 2010)
In the summer of 2001, New York college student Tyler is still feeling lost from the tragedy that has strained his relationship with his father when he meets Ally, a girl who understands his pain. The last thing Tyler's looking for is love, but through their passionate relationship, he finds new possibilities for happiness. It's an unforgettable story about the power of the heart, the strength of family, and the importance of treasuring every day of one's life.